Inidbition of Rhizoctonia solani the Causal Agent for Collar Rot of Teak (Tectona grandis) Seedlings by Fungicides and Biocontrol Agents in In-vitro Conditions - Ramesh, K. R. (Indian Forester, 2000)
A laboratory study was carried out to control the collar rot of Teak (Tectona grandis), which is a major nursery disease in Tamil Nadu caused by Rhizoctonia solani anamorph of Thantephorus cucumeris by use of 6 fungicides, Neem oil, 3 mutants of Trichoderma viride and Pseudomonas fluorescens. Among fungichles testes chlorothalonil (Kavach), methoxyethyl mercury chloride (Emisan-6), mancozeb (lndofil M-45) and carbendazim (Bavistin) were more effective in inhibiting the fungal growth. In biocontrol aspect T. viride MNT-7 followed by T. viride MNT-2 were found to be the most effective in inhibiting the growth of the pathogen. So these may be used in controlling the disease.